OPTIMALISASI LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR: PENGABDIAN MASYARAKAT GURU DI SEKOLAH DASAR - Via Yustitia; Bahauddin Azmy; Feny Rita Fiantika; Danang Prastyo (Universitas Majalengka, 2023)
This community service aims to optimize the school environment as a learning resource. Community Service Activities (PkM) are carried out offline at Kepuh Kirian Elementary School in Surabaya. The activity was attended by 18 teachers from SDN Kepuh Kiriman Surabaya and the event ran smoothly. This activity lasts three months, starting with the provision of material, then the teacher identifies the school environment that can be used as learning study material. Several identification steps were carried out by the workshop participant teachers, namely the workshop participants took inventory of the potential of the school environment as a source of learning, identified and mapped the potential of the school environment as a source of learning according to Basic Competency (KD), structuring the potential of the school environment as a source of learning, conducting evaluations and taking action. Continue the implementation of structuring the potential of the school environment as according to Basic Competency (KD) and relevant subjects.